Investigation and optimization of thermal shock effects on the properties and microstructure of Nanoclay-Glass Fiber Reinforced Epoxy Composites. (11th September 2019) - Shettar, Manjunath; Kini, U Achutha; Sharma, Sathyashankara; Hiremath, Pavan; M C, Gowrishankar
Abstract: In the present work, 'Nanoclay-Glass Fiber Reinforced Epoxy Composites (NGFRECs)' are produced by hand lay-up process with a varying weight percentage of glass fiber and nanoclay. NGFRECs undergo two variety of thermal shock conditions. As prepared composites and thermal shock conditioned specimens are tested for tensile and flexural strength according to ASTM standards. To optimize the responses variables, 'Design of Experiment (DOE)' based on the full factorial design (3 3  = L27 ) is used. MINITAB 18 software is used for design and analyses. Results revealed that increasing glass fiber weight percentage and nanoclay has enhanced the flexural and tensile strength, whereas thermal shock conditions declined aforesaid strengths. The failure mode of the NGFREC as disclosed from SEM images include any of the following combinations, fiber pullout, rupture of the matrix, fiber-matrix de-bonding, delamination, matrix crazing, initiation and propagation of micro-cracks.